Secularism in Bangladesh: an analysis of the views of Ghulam Azam - Kafi, Muhammad Abdullahil (Kulliyyah of Islamic Revealed Knowledge and Heritage, International Islamic University Malaysia, 2011)
The present research explores the contributions of Ghulam Azam (b.1922) to the development of Islamic thought in Bangladesh through his intellectual endeavours and socio-political activities. This paper evaluates critically his discourse on Secularism in Bangladesh which has gained wide acceptance among the educated Bangladeshi Muslim society since the post-independence period. This study is based on the investigation of Ghulam Azam's life, intellectual legacy and religious contributions. Ghulam Azam's theoretical view on Secularism is mainly found in his three books Dhomoniropekkha Motobad (Secularism), Islam and Philosophy, and Islam: The Only Divine and Complete Code of Life and in his biography as well. The research primarily applied a textual analysis method to examine both the primary (i.e. Ghulam Azam's writing) and secondary sources. This study also analyzes the validity of his arguments on Secularism and to introduce his intellectual contributions in international academia. The research finds that he considers Secularism as the major outcome of European Renaissance. He develops a conceptual framework of studying Secularism by considering it as the source of conflict between the Church and science in the medieval period. According to him, Secularism is the outcome of the extreme and primitive thought of Christian priests. Ghulam Azam states that early Secularism proposed the idea of separation of political and religious affairs, whereas modern Secularism declares the denial of religion. According to him, this development occurred due to the clash between the priests' excessive religious thought and modern scientific research in the evolution of contemporary Secularism. Hence, Secularism has contributed to the development of modern scientific revolution. An analysis of Ghulam Azam's views confirms that he bears contemporary Islamic revivalist thought – striving to achieve the integrated development of the Muslim ummah worldwide and re-establish the Muslim civilization based on Islamic revealed knowledge. To sustain the essence of Islamic code of life, he rejects Secularism, considering it as invalid for Muslims and Muslim society. This research evaluates his discourse on Secularism and its significance for the Muslim society in Bangladesh. The intellectual contributions of Ghulam Azam through his writings (mostly in the Bengali language) are found relevant to contemporary Bangladeshi society and often relates to the ongoing conflict between Islam and Secularism there.